The impact of structure adjustment of energy consumption on the structural upgrading of the construction industry - Zenan Qin; Junwei Li (PLoS ONE, 2025)
Using spatial Durbin model on panel data from 30 provinces in China from 2008 to 2022, this article explores the technical effect, price effect, and spatial effect of energy consumption structure on the structure of the construction industry. It is found that structure adjustment of energy consumption (SAEC) has a significant promoting effect on structural upgrading of the construction industry (SUC), exhibiting a negative spillover effect in space. Technology spillovers and research and development (R&D) are also the main channels through which SAEC affects SUC, while the channel effect of energy price effect is not significant. Further research has found that reducing the proportion of coal, oil, and natural gas consumption can promote SUC, with natural gas having the strongest effect. At the regional level, SAEC has a stronger promoting effect on SUC in the central and western regions, but its spatial negative spillover effect is more pronounced in the eastern region; On the temporal level, the promotion effect of SAEC on SUC was stronger from 2008 to 2014, while its spatial negative spillover effect was more pronounced from 2015 to 2022. In addition, with the increase in energy prices and human capital levels, it can further stimulate the promoting effect of SAEC on SUC.